Tales of Two Cities (in the Second-Century BCE): Jerusalem and Nineveh - Dick, Michael Brennan (Journal for the study of the pseudepigrapha, 2016)
This article reviews the two roughly contemporary deutero-canonical works from the second century BCE: the book of Judith and the book of Tobit. Both of these books agree in making Nineveh/Assyria the antagonist, even though the Medes had destroyed that city more than four hundred years before. This article proposes that Nineveh, ‘the evil city’, functions as an antipodal to the Holy City of Jerusalem. Despite the seemingly irresistible imperial power of Assyria embodied in its seventh-century capital, God's plans prophesied through the anti-Assyrian oracles of Isaiah and other prophets will not prove false. This peripeteia culminates in an eschatological New Jerusalem with its thoroughly renewed Temple for its God.